The Relationship Between Menstrual Cycle and Recurrent Aphthous Stomatitis in Students of the Faculty of Dentistry, Syiah Kuala University - Sarinah Rambe; Liza Meutia Sari; Munifah Abdat; Indah Salsabila (FKG Universitas Syiah Kuala, 2024)
Recurrent aphthous stomatitis (RAS) is a painful oral mucosal disorder that affects many people. It is recurrent and appears during childhood or adolescence. Its pathogenesis is characterized by changes in cellular immune response, may explain how the role of sex hormones function during the menstrual cycle. This study aims to investigate the relationship between RAS and the menstrual cycle. The samples were taken from female students of the Faculty of Dentistry, Syiah Kuala University, with a total sample of 191 students who has experienced RAS or had a history of RAS in the past month. This study consisted of two sections of questions, one about the history of RAS and another about the day of menstruation when RAS occurred. The questions were closed-ended, with yes or no answer options. The data were collected using Google Forms. This study showed that 72.8% of subjects were in the luteal phase and 27.2% of subjects were in the follicular phase. Data analysis used the Chi-Square test (p 0.05) as a significant reference. The results of the statistical test showed p = 0.01, CI = 1.22-4.93, OR = 2.45. This showed a significant relationship between the luteal phase of menstruation and RAS. The luteal phase of menstruation had a 2.45 times greater risk of experiencing RAS.